Answer:
(- 3, 4 )
Explanation:
Given the 2 equations
- 3x - y = 5 → (1)
10x + 9y = 6 → (2)
Rearrange (1) expressing y in terms of x by adding 3x to both sides
- y = 5 + 3x ( multiply through by - 1 )
y = - 5 - 3x → (3)
Substitute y = - 5 - 3x into (2)
10x + 9(- 5 - 3x) = 6 ← distribute and simplify left side
10x - 45 - 27x = 6
- 17x - 45 = 6 ( add 45 to both sides )
- 17x = 51 ( divide both sides by - 17 )
x = - 3
Substitute x = - 3 into (3) for corresponding value of y
y = - 5 - 3(- 3) = - 5 + 9 = 4
Solution is (- 3, 4 )